The Dilemma of Religious Education Model in Indonesia Affecting the Inter-Group Attitudes: An Online Survey - Sulaiman Girivirya (AL-ISHLAH: Jurnal Pendidikan, 2022)
Legally, Indonesia adheres to religious education preferences with a mono-religious model. Ideally, every institutionally registered religious believer in Indonesia has the right to get religious education according to their respective religions. This is also in accordance with international human rights law.  The method used for data collection in this study was virtual -questionnaire. The questions on the questionnaire begin with the choice questions and are followed by open-ended questions.  This study found that not all religious people get religious education by their religion. From the results of this study, some respondents had experienced following religious education by their faith, viewed other groups negatively, and were disturbed by the activities of other religious groups. However, in general, this study showed that those in diverse religious groups did not have difficulty in inter-group contact efforts.